THE ROLE AND RESPONSIBILITY OF MUI NORTH SUMATRA IN HALAL CERTIFICATION ISLAMIC LAW AND SHARIAT PERSPECTIVE - Indra Utama Tanjung; M Juang Rambe; Zikri Rizky Maulidin (International Journal of Synergy in Law, Criminal, and Justice, 2024)
This study analyzes the role and responsibilities of the Indonesian Ulema Council (MUI) of North Sumatra in the halal certification process after the enactment of Law No. 33 of 2014 concerning Halal Product Assurance (UU JPH). The JPH Law transfers most of the administrative authority of halal certification to the Halal Product Assurance Organizing Agency (BPJPH), but the MUI still plays a crucial role in issuing halal fatwas that form the basis for certification. In its implementation, the MUI of North Sumatra faces a number of challenges, including complex coordination with BPJPH, the length of the certification process due to complicated bureaucracy, and the lack of competent resources and auditors. In addition, the issue of transparency in the certification process and ineffective socialization regarding the new regulations are also significant obstacles. This study recommends strengthening the internal capacity of the MUI of North Sumatra, increasing transparency and accountability in the halal certification process, and improving coordination with BPJPH to reduce bureaucratic obstacles. In addition, increasing socialization to business actors regarding the new procedures in halal certification is very necessary to ensure the effectiveness of the implementation of the JPH Law and maintain public trust in halal certification institutions. With these steps, it is hoped that the MUI of North Sumatra can continue to carry out its role in ensuring the halalness of products more efficiently and reliably.